Rwanda Economic Update, No. 7 : Managing Uncertainty for Growth and Poverty Reduction - World Bank Group (Kigali, Rwanda, 2015)
The Rwanda Economic Update reports on and synthesizes recent economic developments and places them in a medium-term and global context. It analyzes the implications of these developments and policies for the outlook for Rwanda s economy. Rwanda s economic growth recovered in the first three quarters of 2014. The economy grew 7.1 percent. Faster GDP growth reflected higher growth of the services sector, at 9.1 percent, up from 5.4 percent in 2013, when the economy suffered from the lagged impact of the 2012 aid shortfall. The first section on macroeconomic issues of this edition of the Rwanda Economic Update examines two key questions: What led to the growth recovery in the first three quarters of 2014, and what are growth prospects for 2014, 2015, and 2016? The growth recovery mainly reflected increased government expenditure, which boosted domestic demand such as private consumption and investment. The expansion of domestic demand was partially offset by lower external demand for Rwanda s traditional commodities. Higher government expenditure contributed to growth recovery in the services sector through government consumption of private services. Inflation declined throughout 2014, reflecting lower growth in import prices. The recent decline in oil prices is expected to contribute not only to lower inflation but also to more stable exchange rate, an improved balance of payments, and smaller electricity subsidies. The special focus section of this report identifies and quantifies risks in the agriculture sector, with targeted interventions that complement the lessons learned under PSTA 2/CAADP 1 to more effectively manage these risks and to achieve further growth in the agriculture sector.